Designing Active and Stable Silicon Photocathodes for Solar Hydrogen Production Using Molybdenum Sulfide Nanomaterials. Issue 18 (8th August 2014) - Benck, Jesse D.; Lee, Sang Chul; Fong, Kara D.; Kibsgaard, Jakob; Sinclair, Robert; Jaramillo, Thomas F.
<x xml:space="preserve">Abstract</x> Silicon is a promising photocathode for tandem photoelectrochemical water splitting devices, but efficient catalysis and long term stability remain key challenges. Here, it is demonstrated that with appropriately engineered interfaces, molybdenum sulfide nanomaterials can provide both corrosion protection and catalytic activity in silicon photocathodes. Using a thin MoS2 surface protecting layer, MoS2‐n+p Si electrodes that show no loss in performance after 100 h of operation are created. Transmission electron microscopy measurements show the atomic structure of the device surface and reveal the characteristics of the MoS2 layer that provide both catalytic activity and excellent stability. In spite of a low concentration of exposed catalytically active sites, these electrodes possess the best performance of any precious metal‐free silicon photocathodes with demonstrated long term stability to date. To further improve efficiency, a second molybdenum sulfide nanomaterial, highly catalytically active [Mo3S13]2− clusters, is incorporated. These photocathodes offer a promising pathway towards sustainable hydrogen production.